Cultural tourism: A methodological approach based on the knowledge of its demand - María Dolores Sánchez-Sánchez (Harvard Deusto Business Research, 2020)
The aim of this research is to propose and validate a conceptual model that measures the degree of satisfaction of cultural tourists. The model could help us to better understand this segment of the market and identify factors that explain the degree of customer satisfaction. In terms of methodology, a hypothetical-deductive method has been applied. After reviewing the literature, five hypotheses have been proposed, integrated into an exploratory model. The model has been validated by a structural equations model (SEM) and estimated with data from the Survey on Resident Tourism/FAMILITUR, conducted by the Spanish National Statistics Institute (INE). The results assess the significance of sociocultural variables and tourist experience, and the null influence of satisfaction as a predictor of repeat visits. The model permits confirming a set of appropriate variables to analyze the satisfaction of Spanish internal demand with a cultural motivation, on local trips. Given the growing importance of cultural tourism worldwide, the proposed model can become an interesting tool for the management of the touristic positioning of destinations with a cultural heritage, as it helps us to understand the satisfaction and loyalty of the tourist flow.